Herbicides for Highway Rights-of-Way - Jason A. Ferrell; Kenneth A. Langeland (EDIS)
SS-AGR-271, a 3-page fact sheet by J. A. Ferrell and K. A. Langeland, provides a table of recommendations for postemergence broadcast applications. Published by the UF Department of Agronomy, July 2007.